Cultural Clash and Self-Discovery: A Multicultural Study of Amy Tan's the Joy Luck Club - Ali Kareem, Ammar; Asadi Amjad, Fazel (International Journal of Psychosocial Rehabilitation, 2020)
Some scholars and theorists believe that the clash of cultures due to wars and the wave of migration is a healthy process since it ostensibly dissolves cultural differences. Yet, this article argues that cultural clashes may also generate passive phenomena due to cultural imposition, which is vividly loaded with a lot of negative consequences that unveil the real aim of the colonial project. To prove the negative aftermath of such a phenomenon, Frantz Fanon's term of cultural imposition has been applied to Amy Tan's novel The Joy Luck Club within a postcolonial context. The article also aims at showing that the imposition of a certain culture on another culture may endanger a sense of inferiority complex, stereotyping, and double consciousness. The article furthermore gives the scholars and researchers a conspicuous view that the term cultural imposition can also be applied to literature alongside nursing. The present article proves that Tan's characters suffer in a world that considers them as aliens due to their complexion, language, and even their behavior.